2017
DOI: 10.1002/2016pa002955
|View full text |Cite
|
Sign up to set email alerts
|

Paleoproductivity in the northwestern Pacific Ocean during the Pliocene‐Pleistocene climate transition (3.0–1.8 Ma)

Abstract: Alkenone mass accumulation rates (MARs) provide a proxy for export productivity in the northwestern Pacific (Ocean Drilling Program Site 1208) spanning the late Pliocene through early Pleistocene (3.0–1.8 Ma). We investigate changes in productivity associated with global cooling during the onset and expansion of Northern Hemisphere glaciation (NHG). Alkenone MARs vary on obliquity timescales throughout, but the amplitude increases at 2.75 Ma concurrent with the intensification of NHG and cooling of the sea sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…On geologic time scales, changes in the strength and position of the Kuroshio Current system demonstrates clear glacial/interglacial variability (e.g., Hoiles et al., 2012; Kawahata & Ohshima, 2002, 2004; Kitamura & Kimoto, 2006; Kitamura et al., 1999; Yamamoto et al., 2005). Specifically, proxy data indicate changes in surface water hydrology, paleoproductivity, pollen accumulation, and wind intensity at sites along this frontal boundary (Abell et al., 2021; Gallagher et al., 2015; Kawahata & Ohshima, 2002; Venti & Billups, 2013; Venti et al., 2006, 2017). This variability appears to be associated with the amplification of the East Asian winter monsoon season and increased thermal gradients between low and high latitudes (Abell et al., 2021; Venti et al., 2013, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On geologic time scales, changes in the strength and position of the Kuroshio Current system demonstrates clear glacial/interglacial variability (e.g., Hoiles et al., 2012; Kawahata & Ohshima, 2002, 2004; Kitamura & Kimoto, 2006; Kitamura et al., 1999; Yamamoto et al., 2005). Specifically, proxy data indicate changes in surface water hydrology, paleoproductivity, pollen accumulation, and wind intensity at sites along this frontal boundary (Abell et al., 2021; Gallagher et al., 2015; Kawahata & Ohshima, 2002; Venti & Billups, 2013; Venti et al., 2006, 2017). This variability appears to be associated with the amplification of the East Asian winter monsoon season and increased thermal gradients between low and high latitudes (Abell et al., 2021; Venti et al., 2013, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, proxy data indicate changes in surface water hydrology, paleoproductivity, pollen accumulation, and wind intensity at sites along this frontal boundary (Abell et al., 2021; Gallagher et al., 2015; Kawahata & Ohshima, 2002; Venti & Billups, 2013; Venti et al., 2006, 2017). This variability appears to be associated with the amplification of the East Asian winter monsoon season and increased thermal gradients between low and high latitudes (Abell et al., 2021; Venti et al., 2013, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Using alkenone data, Abell et al (2021) found that cooling at Hole 1208A corresponded to NHG and a southward shift of westerly winds. Alkenone mass accumulation rates estimated for Hole 1208A indicate well-developed 40 kyr paleoproductivity cycles, with higher productivity during growth of Northern Hemisphere ice (Abell et al, 2021;Venti et al, 2017). Planktic foraminifera evolutionary data conducted at three deep sea sites spanning the KCE indicate a period of increased evolutionary turnover within the region from 5 to 2.5 Ma, a time encompassing tectonic gateway closures and climate shifts, hinting that major changes took place within the current in response to these abiotic factors (Lam & Leckie, 2020a;Lam et al, 2020).…”
mentioning
confidence: 99%
“…However, there is not a common repository for paleoceanographic data and publications, and this lack of centralization limits the efficacy of the earth science community in directing research efforts. For the North Pacific, such ongoing mechanistic hypotheses include deep ocean circulation (e.g., Rae et al, 2014;De Pol-Holz et al, 2006), deep water and intermediate water formation and ventilation (e.g., Knudson and Ravelo, 2015a;Zheng et al, 2000;Cook et al, 2016), and changes in the oceanicpreformed nutrient inventories (e.g., Jaccard and Galbraith, 2013;Knudson and Ravelo, 2015b), as well as more regional mechanisms such as sea ice extent (e.g., Max et al, 2012), upwelling intensity (e.g., Di Lorenzo et al, 2008;Hendy et al, 2004), local surface ocean productivity (e.g., Serno et al, 2014;Venti et al, 2017), and terrigenous and marine fluxes of iron (e.g., Davies et al, 2011;Praetorius et al, 2015).…”
Section: Introductionmentioning
confidence: 99%